Mechanisms of micro-voids formation caused by optical breakdown in KCl single crystals under laser emission - Volosyuk, М.A. (Вопросы атомной науки и техники, 2014)
The phenomenon of optical breakdown has been studied experimentally for KCl single crystals exposed to laser emission focused on the neodymium glass with modulated quality-factor, pulse duration 5·10⁻⁸ s, wavelength λ = 1054 nm, and pulse energy of the order 1 J in the regime of local intrinsic absorption of the laser emission by the single crystal. Evaluations of local heat flash energetic constituents and characteristic durations for both local area heating and relaxation processes and following comparison with experimental results have shown that the relaxation process takes place in two stages: the first is fast phase followed by crowdion mass transfer with shock wave participation, and the second is slow phase with participation also dislocation mass transfer.